2015
DOI: 10.1007/s13277-015-4238-9
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 10 gene −1082A/G polymorphism is associated with osteosarcoma risk and poor outcomes in the Chinese population

Abstract: Interleukin-10 (IL-10) is a multifunctional cytokine that participates in the development and progression of various malignant tumors. However, data regarding the role of IL-10 polymorphisms in osteosarcoma development are not available. A case-control study was conducted in 260 patients with osteosarcoma and 260 healthy controls to investigate the possible association between IL-10 polymorphisms and the risk of osteosarcoma. Our results indicate the IL-10 -1082A/G (rs1800896) polymorphism is significantly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…A total of nine studies [ 26 , 29 , 32 , 33 , 36 40 ] with 1119 cases and 1358 controls were recruited in this meta-analysis. The process of study selection and the inclusion process are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of nine studies [ 26 , 29 , 32 , 33 , 36 40 ] with 1119 cases and 1358 controls were recruited in this meta-analysis. The process of study selection and the inclusion process are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Ma et al [ 38 ], Xu et al [ 39 ] and Wu et al [ 40 ] reported the alleles and genotypes of TGF-β1 29T/C polymorphism. Oliveira et al [ 26 ] reported the alleles and genotypes of IL-6 174G/C and IL-10 1082A/G polymorphism, and these two polymorphisms were also studied by Qi et al [ 32 ] and Cui et al [ 33 ]. Furthermore, seven studies [ 29 , 32 , 33 , 37 – 40 ] were performed in Asian populations, and the other two studies [ 26 , 36 ] were conducted in Caucasian populations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, 53 articles were included in the final meta-analysis. Of these 53 articles, 24 articles [ 40 63 ] include 26 studies examining IL-10 -1082A/G polymorphism, 28 articles [ 18 , 42 , 43 , 45 , 47 , 49 , 52 , 53 , 57 - 61 , 63 - 77 ] include 33 studies examining the -819T/C polymorphism, and 39 articles [ 18 , 42 , 43 , 45 , 47 , 52 , 53 , 56 - 67 , 69 , 70 , 73 - 76 , 78 - 91 ] include 42 studies examining the -592A/C polymorphism (Table 1 ). Of the 53 articles, two publications [ 18 , 45 ] with three cancer types were considered as three studies and one publication [ 65 ] with two cancer types were also considered as two studies.…”
Section: Resultsmentioning
confidence: 99%
“…For the studies assessing three polymorphisms (-1082A/G, -819T/C and -592A/C) [ 32 , 37 ], two (-1082A/G and -592A/C) [ 31 ], only one such as -1082A/G [ 29 , 30 , 33 - 35 , 38 ] or -819T/C [ 36 , 39 ] polymorphism and cancer risk but no other IL-10 gene polymorphisms, the genotypes distribution in the controls were deviated from HWE, thus, these studies were excluded in the final analysis. Sixteen studies were also deviated from HWE, but the genotypes distribution in the controls of eight studies [ 18 , 64 - 67 , 70 , 73 , 76 ] were consistent with that expected from the HWE for both -819T/C and -592A/C polymorphisms, five [ 81 , 84 , 86 , 87 , 90 ] for the -592A/C polymorphism and three [ 41 , 48 , 54 ] for the -1082A/G polymorphism, thus, these studies were included in the final analysis. For those studies [ 18 , 45 , 65 ] with the same control subjects, the control numbers were calculated once in the total number.…”
Section: Resultsmentioning
confidence: 99%